Photocatalytic composites based on titania nanoparticles and carbon nanomaterials. (14th April 2015) - Nguyen, Bich Ha; Nguyen, Van Hieu; Vu, Dinh Lam
Abstract: In this article we present a review on recent experimental works toward the formation of visible light responsive composite photocatalysts on the basis of titania nanoparticles and carbon nanomaterials of different types. The research results achieved in last years has shown that the nanocomposite photocatalysts comprising titania nanoparticles and graphene or graphene oxide sheets, and also nanoparticles of noble metals and metallic oxides, exhibited the evident priority compared to the others. Therefore our review emphasizes the research on these promising visible light responsive nanophotocatalysts.